Perbedaan Motivasi Belajar Dan Minat Belajar Antara Siswa Yang Belajar Daring Dan Luring Pada Pelajaran Bahasa Indonesia Di SMP Swasta Katolik Budi Murni 3 Medan - Sonni Willi Munte; Risydah Fadilah; Rahmi Lubis (Mahesa Research Center, 2022)
This study uses a quantitative approach, with the sampling technique used is accidental sampling. The population in this study amounted to 216 and the sample from class VIII was 54 which was divided into 2 groups, namely 27 data from each group. The analytical method used to analyze the data obtained in this study uses the Mann Whitney U analysis method. This type of research uses the theoretical basis of learning motivation and interest in learning based on aspects of the theory of Martaniah (2006) and Slameto (2013). The results of this study indicate that the significance value of Mann Whitney U is 0.924, which means that the difference between learning motivation in students who study online and offline is rejected. Thus, the results of the study in the interest in learning group showed the significance value of Mann Whitney U was obtained at 0.808, which means that there is no difference between students' interest in learning when studying online and offline, meaning that this study was rejected because it was not in accordance with the initial hypothesis.